Solidarity intermediation for food marketing: A work experience between production companies from the northern peri-urban area of ​​Santa Fe and technical teams in the period 2020-2022 (Papeles, 2023)
This article presents an analysis of solidarity intermediation in a short food marketing circuit that was built in conjunction with the members of  producers fair in the northern peri-urban area of ​​Santa Fe, located in Monte Vera, and the technical teams of state and non-state institutions. From the actions linked to marketing support, at the beginning of the pandemic, we realize how the formation of a network framework contributes to the formation of food distribution nodes coming from the work of a group of women in the period 2020 -2022.
Keywords: solidarity intermediation; marketing; fairs